AN ELEMENTARY DEMONSTRATION OF THE FRIENDSHIP THEOREM USING GRAPHS WITH AN APPLICATION IN EXPERIMENTAL DESIGNS - SPURI, Jéssica; CHAVES, Lucas Monteiro (Brazilian Journal of Biometrics, 2022)
One proof of the friendship theorem, a classical result in combinatorics, is presented. Graphs are intensively used to explain all the steps of the demonstration and thus make it more intuitive. An application in experimental designs is presented.